ASPAC: Swedish-Serbian (cyrillic) - Språkbanken Text (University of Gothenburg, 2024)
Part of The Amsterdam Slavic Parallel Aligned Corpus

Del av The Amsterdam Slavic Parallel Aligned Corpus
ASPAC: svenska-serbiska (kyrilliskt)
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik